The Influence of the Online Game Mobile Legend on Students' Attitudes in Islamic Religious Education Subjects at Muhammadiyah Middle School in Parepare - Rahmaniah, Rahmaniah; Muis, Andi Abd.; Zaid, Muhammad; Herman, Sudirman; Da’te, Nurhidayah; Marasabessy, Nafsia; Assam, Abdul (The Future of Education Journal, 2025)
The aim of this thesis research is to find out Mobile Legend games are used among Muhammadiyah Parepare Middle School students. The type of research used was field research conducted at Parepare Muhammadiyah Middle School, using a quantitative approach, there were two data sources used, namely primary data sources including students and teachers in Islamic Religious Education subjects and secondary data sources including documentation results and various literature. in the form of books, journals, articles related to research, research instruments used, namely the researcher himself, questionnaire sheets, documentation guidelines, interview guidelines and documentation guidelines. The data analysis techniques used are descriptive analysis techniques and analysis requirements tests The results of the research obtained are that the use of Mobile Legend Online Games at Muhammadiyah Parepare Middle School is 41.7%, the influence of Mobile Legend online games on students' attitudes is 17.4%, the solutions in overcoming the negative influence of Mobile Legend games on students' learning attitudes, namely, limiting playing time, increasing parental involvement and having positive activities at school that can distract students from playing games, especially Mobile Legend games.